Comparative Study on the Harmonization of Resource- Utilization in the Case of Three Companies in the European Automotive Industry - Bogdan Cosmin GOMOI (CECCAR Business Review)

(untitled)
The European automotive industry has faced two major challenges over the past five years, the COVID-19 pandemic and the increased competition in this business sector, respectively, following the emergence of new models, including electric and hybrid vehicles. Thus, while 2020 saw a decline in sales due to the pandemic, they began to increase again, gradually, starting with 2021, being however impeded by a shortage of semiconductors. It can be argued that only 2023 marks a relative stability of car sales at European Union level. France, Germany, and Italy are three strong, comparable EU member states, with a renowned automotive industry. This study aims to highlight the financial path, in terms of resourceutilization, of three relevant companies in this field, namely, Renault, from France, Volkswagen, from Germany, and Stellantis, from Italy. The targeted time frame spans from 2020 to 2023, featuring both the pandemic context and the gradual recovery that followed. The financial harmonization of the resource-utilization is highlighted both statically and dynamically, using static financial indicators (structure of uses and resources, liquidity, solvency, and financial balance) and dynamic methods (absolute and relative deviations and average increase/decline rates).